Genetic footprints of T cell exhaustion - Buggert, Marcus; Tauriainen, Johanna; Karlsson, Annika C. (Translational Cancer Research, 2017)
In a recent publication in Science, Haining and colleagues describe for the first time the epigenetic landscape of exhausted CD8+ T cells in chronic viral infections (1). The results shed some light on how exhausted T cells could be “epigenetically” engineered in chronic viral or cancer immunotherapies.